2009
DOI: 10.1159/000229973
|View full text |Cite
|
Sign up to set email alerts
|

A New Prediction Model of Postoperative Complications after Major Hepatectomy for Hepatocellular Carcinoma

Abstract: Background/Aims: Serum hyaluronic acid (HA) concentrations reflect the degree of hepatic dysfunction and may have potential for predicting postoperative complications in a major hepatectomy for hepatocellular carcinoma (HCC). Methods: Serum HA concentrations and other conventional liver function tests were measured prior to major hepatectomies in 52 patients. Independent predictors for postoperative complications were analyzed and the discriminant equation was established and validated. Results: Postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Several prediction models for postoperative morbidity in general surgery, cardiac surgery, and hepatocellular carcinoma populations have been introduced [8,9,13]. However, the aforementioned models cannot reliably be used in gynecological oncology [21,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prediction models for postoperative morbidity in general surgery, cardiac surgery, and hepatocellular carcinoma populations have been introduced [8,9,13]. However, the aforementioned models cannot reliably be used in gynecological oncology [21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Several prediction models using the identified risk factors have been suggested to forecast the occurrence of postoperative morbidity in general surgery [810], cardiac surgery [11], esophageal cancer surgery [12], and hepatocelluar cancer surgery [13]. However, the individualized prediction models for morbidity after gynecologic cancer surgery are relatively rare [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…At our institution, anatomical resections were basically planned for HCC if the liver function was well preserved and the estimated remnant liver volume met our previously established criteria . The indications for hepatectomy were evaluated according to the extent of tumor progression, liver function and general condition of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…An excess infusion volume, splenectomy and lymphatic leakage from the resected surfaces of the liver or hepatic ligament may also be risk factors for PLA. Although recent studies have demonstrated that an elevated serum level of hyaluronic acid (HA) can predict complications after LR for patients with HCC [8] , there is no study that has reported that HA is closely associated with PLA. In addition, few studies investigated whether PLA is a useful prognostic factor in HCC patients undergoing LR.…”
Section: Introductionmentioning
confidence: 99%